BERBAGAI FUNGSI ORGAN PENGAWAS DALAM KONSEP GOOD CORPORATE GOVERNANCE - Sofyan Syafri Harahap (Media Riset Bisnis & Manajemen, 2001)
The efficacy of Board of Commissioner in executing its control funclion has many prob- lems. Due to the lack of expertise of members. To solve this issue, the regulator encour- ages to establish audit commitee to link Board of Commissioner Board of Director and intenal audit function. The paper discuss how to optimize the control function in "good corporate govermmentenvironment by maintaining the good relationship between Board of Commissioner and Independent Auditor.